Kinerja Operasi Aerated Drilling Pada Sumur N di Lapangan Panas Bumi K - Riviani Kusumawardani; Bambang Kustono; Kris Pudyastuti (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2015)
Well N is one of wells in Geothermal Field K. Geothermal Field K located in Muara Enim, SouthSumatera. Well N drilled to 2700 mKU / 2425 mKT. By using aerated drilling techniques, well Nplanned to be completed until 56 days. The main objective on the use of aerated drilling in well N isto reduce the zone with weak pressure formation or zone which have some sort of problem lostcirculation, especially the total lost circulation. In addition, the use of this system is expected to liftcuttings from the loss circulation zone to the surface. The step is parameters analysis which canevaluated performance of aerated drilling operation such as gas injection volume, density and airvolumetric rate, fraction fluids of aerated, aerated viscosity, flow rate and pattern of aerated,concentration of cuttings (Cc) in bore hole annulus, transport cutting ratio (Ft), and rate of cuttinglifting. From the evaluation and optimization analysis from five parameters in aerated drillingoperation at 17 ½”, 12 ¼” and 9 5/8” traject, can be known that cutting lifting has been optimumbecause parameters from the calculations showed fluids flow in annulus (Vann) is more thancutting lifting minimum (Vmin), concentration of cuttings (Cc) is